A nexus between macroeconomic dynamics and trade openness: moderating role of institutional quality. Issue 6 (30th April 2021) - Zhuang, Yu; Yang, Shuili; Chupradit, Supat; Nawaz, Muhammad Atif; Xiong, Rong; Koksal, Cihat
Abstract : Purpose: First, the current study contributes to the available debate by reinvestigating the impact of economic growth (EG), foreign direct investment (FDI), technological innovation (TI) and inflation (INF) on trade openness (TO). Second, the study tests the moderating role of institutional quality (INS) on the relationship among EG, FDI, TI and TO. Third, the study tests how TO contributes to EG efficiency. Design/methodology/approach: The study collects the data from the group of twenty (G20) economies for the period of 1998–2020. The study applied the Kao (1999), Pedroni (2001), and Palamuleni (2017) cointegration tests to test the long-run association between variables. The study applied fully modified least square (FMOLS) and dynamic least square (DOLS) models to test the hypotheses. Findings: Findings of the study showed the positive impact of EG, FDI and TI on TO, which becomes more positive in the presence of institutional quality. Results indicate that INS plays an enhancing role in the relationship between FDI and TO, EG and TO and TI and TO. The study showed a negative relationship between INF and TO, and institutional quality plays a buffering role in the relationship between INF and TO. Originality/value: First, the study reinvestigates the empirical association among EG, FDI, TI, INF and TO. Second, the study tests the moderating role of INS on the relationship between the proposed variables by developing an index of all the indicators of INS. Third, the study tests the contributions of TO in economic efficiency (ECE). The contributions of the present study will increase the available literature of TO and help the policy makers of G20 nations to suggest important policies to promote TO and ECE.